Analisis Model Bisnis dan Perencanaan Pengolahan Sampah Plastik PT. Perangkat Perkasa Indonesia - Rus Bintoro; Eli Suherli; Dedi Prayitno; Agung Yuliyanto Nugroho (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
The increasing accumulation of plastic waste each year has become a serious environmental and public health issue. PT. Perangkat Perkasa Indonesia recognizes a sustainable business opportunity through the processing of plastic waste into economically valuable products. This study aims to analyze the business planning strategies implemented by the company in managing its plastic waste processing operations, covering market analysis, operational planning, financial projections, and marketing strategies. A qualitative descriptive method was used, with a case study approach at PT. Perangkat Perkasa Indonesia. Data were collected through interviews, observations, and document analysis. The results indicate that the company has significant potential to develop a plastic recycling business supported by human resources, appropriate technology, and increasing public awareness regarding waste management. An integrated and well-structured business plan is key to building a business model that is not only financially profitable but also environmentally impactful. This research recommends strengthening promotional strategies and collaboration with third parties to expand market reach and improve operational efficiency.